2019
DOI: 10.4168/aair.2019.11.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adult Severe Refractory Asthma in Korea Analyzed From the Severe Asthma Registry

Abstract: PurposeAlthough mild to moderate asthma is much more common, the morbidity and mortality of severe asthma are much higher. This study was performed to identify and analyze the clinical characteristics of severe asthma in Korea.MethodsWe registered patients with severe refractory asthma into the Severe Asthma Registry supported by the Severe Asthma Work Group of the Korean Academy of Asthma, Allergy and Clinical Immunology. Patients were enrolled since 2010 from the 15 university hospitals nationwide in Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…In the current study, patients with SA as per the modified ERS/ATS 2014 criteria were predominantly female, overweight/obese, in the 5th decade of life, with mean age of onset of symptoms at 15 years, confirming an older population with long-lasting asthma. Our cohort is therefore comparable to other SA cohorts (22)(23)(24), where the mean age of patients with SA was also over 50 years. A recent cross-sectional review of the ProAR cohort compared all subjects using different classification criteria, and reclassified patients according to ATS 2000 severe asthma criteria (11), criteria proposed to WHO in 2010 and ERS/ATS criteria 2014.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, patients with SA as per the modified ERS/ATS 2014 criteria were predominantly female, overweight/obese, in the 5th decade of life, with mean age of onset of symptoms at 15 years, confirming an older population with long-lasting asthma. Our cohort is therefore comparable to other SA cohorts (22)(23)(24), where the mean age of patients with SA was also over 50 years. A recent cross-sectional review of the ProAR cohort compared all subjects using different classification criteria, and reclassified patients according to ATS 2000 severe asthma criteria (11), criteria proposed to WHO in 2010 and ERS/ATS criteria 2014.…”
Section: Discussionsupporting
confidence: 77%
“…This study showed a higher proportion of patient (78%) that had at least one asthma exacerbation in the previous year. Indeed, the literature also points to a high number of SA patients experiencing exacerbations in other cohorts, with 41% to 83% of SA patients reporting at least one exacerbation in the last year in these studies (22)(23)(24)28,32). Although the frequency reported varied among studies, probably because of methodological differences and definition of exacerbations, all studies report that these patients are experiencing a high frequency of exacerbations, highlighting what is still an unmet need for these patients.…”
Section: Discussionmentioning
confidence: 90%
“…Average annual use of oral steroids has been estimated at 10.5 treatment episodes per patient. 15 In the Korean Severe Asthma Registry, chronic OCS use was found to be 18% among those in GINA step 4 or 5 treatment levels 45 as compared to Taiwanese severe asthmatic patients, where the rate of OCS prescriptions in the previous year reached almost 50%. 46 While robust data regarding the ongoing use of OCS is lacking, it can be safely concluded that the burden of OCS use in our population is high.…”
Section: Oral Steroid Use and Asthma Phenotype In Asiamentioning
confidence: 99%
“… 20 In the Korean Severe Asthma Registry, 60.1% of patients at GINA step 5 took OCS continuously. 21 A population-based matched cohort study from Korea revealed that long-term use of SCS was associated with an increased mortality risk in a dose-dependent manner in patients with asthma. 22 Moreover, quantitative studies reported that exacerbation of asthma and long-term OCS-use negatively impacted professional life and made maintaining a normal life challenging.…”
Section: Definition Prevalence and Burden Of Samentioning
confidence: 99%